PENGARUH ULASAN KONSUMEN DAN VISUAL KONTEN TERHADAP MINAT PEMBELIAN PRODUK KULINER LAMPUNG MELALUI SOCIAL COMMERCE DI TIKTOK SHOP PADA MASYARAKAT KOTA BANDAR LAMPUNG - Ferdi, Wahyu; Permatasari, Berlintina; Saputra, Febrian Eko (Journals of Economics and Business, 2024)
This research aims to test the influence of consumer reviews and visual content on interest in purchasing Lampung culinary products through Social Commerce at the TikTok Shop among the people of Bandar Lampung city. In determining the number of samples in determining respondents, researchers used the Hair theory in Ferdinand's book (2006), namely the number of indicators multiplied by 5 to 10. In this study there were 13 indicators, so the number of respondents was 130 respondents. This research method uses a quantitative approach using primary data in the form of a questionnaire distributed to the entire research population. The data in this research will be tested using several stages of testing, including descriptive statistical tests, data quality tests consisting of (validity test, reliability test), and testing all hypotheses through the coefficient of determination test, partial test (t test) and simultaneous test ( f test). The results of this research show that consumer reviews and visual content together have a positive and significant effect on purchasing interest in Social Commerce among the people of Bandar Lampung city. Keywords: Consumer Reviews, Visual Content, Purchase Interest